Glucocorticoid treatment in horses with asthma: A narrative review - Sophie Mainguy‐Seers; Jean‐Pierre Lavoie (Journal of Veterinary Internal Medicine, 2021)
Abstract Despite substantial research efforts to improve the treatment and outcome of horses with asthma, glucocorticoids (GC) remain the cornerstone of drug treatment of this prevalent disease. The high efficacy of GC to relieve airway obstruction explains their extensive use despite potential deleterious effects. However, much is yet to be uncovered concerning GC use in horses with asthma, including the comparative efficacy of the different drugs, the determination of minimal effective doses and the mechanisms underlying their variable modulation of airway inflammation. The objectives of this structured review were to report and compare the plethora of effects of the various GC used in asthmatic horses with a focus on impact on lung function, airway inflammation, and bronchial remodeling. Adverse effects are also briefly described, with an emphasis on those that have been specifically reported in horses with asthma. Ultimately, we aimed to highlight gaps in the literature and to identify future research areas.